The Effect of Hydroquinone Extracted from Sonneratia caseolaris Fruit on the Hemolymph of Tiger Prawn, Penaeus monodon Fab., Infected by Vibrio harveyi - Arifuddin, .; Sukenda, .; Dana, D. (Jurnal Akuakultur Indonesia, 2004)
Study on the effect of hydroquinone extracted from 5. caseolaris fruit on Penaeus monodon immune system was carried out. Hydroquinone was extracted by methanol and chloroform using a soxhlet apparatus. Two kinds of in vivo experiments were conducted that were (1) shrimps were only injected with hidroquinone and (2) shrimps were injected with hidroquinone and challenged with Vibrio harveyi. Total hemocyte, differential hemocyte and phagocytic index were examined on shrimp injected with only hidroquinone and shrimp injected with hidroquinone and challenged with V. harveyi. Total hemocyte of hydroquinone injected shrimp increased significantly by day 5 from 8.33xl06 to 4,93 x 107 cells/ml. Hyaline and semi granular hemocyte cells by day 7 decreased from 61,15% to 27,84% and 8,14% to 2,53%, respectively. However, granular hemocyte cells increase significantly from 30,71% to 69,63%. Phagocytic index increased significantly by day 7 from 0.41 to 0,76. These findings indicated that crude hydroquinone can increase non spesifik imune response of P. monodon against V. harveyi infection. Key words: hydroquinone. Sonneratia caseolaris. Vibrio harveyi, Penaeus monodon, immune system   ABSTRAK Kajian tentang efek hidrokuinon yang diekstraksi dari buah S. caseolaris pada sistem imun udang windu, Penaeus monodon, dilakukan. Hidrokuinon diekstraksi dengan methanol dan kloroform. Dua jenis percobaan in vivo dilakukan yaitu (1) udang hanya diinjeksi dengan hidrokuinon (2) udang diinjeksi dengan hidrokuinon kemudian diuji tantang dengan bakteri Vibrio harveyi. Total hemosit, diferensial hemosit dan indeks pagositas diperiksa pada udang yang dinjeksi dengan hidrokuinon saja dan pada udang yang diinjeksi dengan hidrokuinon dan diuji tantang dengan bakteri V. harveyi. Total hemosit meningkat secara nyata sampai hari ke 5 dari 8,33 x I06 ke 4,93 x 107 sel/ml. Hyaline dan sel-sel semi granular sampai hari ke 7 masing-masing turun dari 61,15% ke 27,84% dan 8,14% ke 2,53%. Hasil ini menunjukkan bahwa hidrokuinon dapat meningkatkan respon imun spesifik pada udang terhadap infeksi V. harveyi. Kata kunci: hidrokuinon, Sonneratia caseolaris, Vibrio harveyi, Penaeus monodon, sistem imun